(untitled) (Global Journal of Management and Business Research, 2019)
This paper is aimed at examining the roles played by school principals in improving students academic achievement in secondary schools of Sidama zone in Southern Nations Nationalities and Peoples Region of Ethiopia It is a mixed type of research which employed both qualitative and quantitative data The findings of the study indicated that school principals have not adequately played roles expected of them to improve students performance Most of them do not have adequate training in school management and are subject teachers who were currently promoted to principal-ship position They attempted to maintain their status quo rather than introducing changes Those challenges hindering school principals from promoting students academic performance do exist at the moderate level and some of the major challenges were large class size failure to introduce new programs to school curriculum lack of commitment on the part of school community and lack of school pedagogical centers